2018
DOI: 10.1002/ange.201801963
|View full text |Cite
|
Sign up to set email alerts
|

Highly Stereoselective Synthesis of 1,3‐Dienes through an Aryl to Vinyl 1,4‐Palladium Migration/Heck Sequence

Abstract: An efficient aryl to vinyl 1,4-palladium migration/ Heck sequence was developed for the stereoselective synthesis of 1,3-dienes.High stereoselectivity was observed not only for 1,3-dienes bearing two similar aryl groups at terminal positions,b ut also for those with configurations shown to be unfavorable with previous methods. Scheme 1. Stereoselectivity control in the transition-metal-catalyzed direct cross-couplingo ftwo different olefins.Supportinginformation and the ORCID identification number(s) for the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 63 publications
(37 reference statements)
0
8
0
Order By: Relevance
“…These results indicated that a CMD (concerted metallation deprotonation) mechanism might be involved in this 1,4‐Pd migration process. The authors also realized a stereoselective synthesis of 1,3‐diene via aryl to vinyl 1,4‐Pd migration, terminated by Heck reaction with acrylates (Scheme ) …”
Section: 4‐palladium Migration Reactionsmentioning
confidence: 99%
“…These results indicated that a CMD (concerted metallation deprotonation) mechanism might be involved in this 1,4‐Pd migration process. The authors also realized a stereoselective synthesis of 1,3‐diene via aryl to vinyl 1,4‐Pd migration, terminated by Heck reaction with acrylates (Scheme ) …”
Section: 4‐palladium Migration Reactionsmentioning
confidence: 99%
“…Starting from the aryl rhodium intermediate Int0,w hich was generated by transmetalation between rhodium catalyst and arylboronic acid 6a, [23] twodifferent pathways A and B would afford direct 1,4-addition product 8a and 1,4-rhodium migration/1,4-addition product 7a,r espectively.I nt he pathway A, the overall energy barrier for the direct insertion of 2cyclohexenone to CÀRh bond is 23.1 kcal mol À1 .While in the pathway B,the 1,4-rhodium migration of Int0 includes aC ÀH oxidative addition [4] and H-transfer sequence with an overall energy barrier of 21.1 kcal mol À1 , [4,15] which is slightly lower than the direct addition process.T he resulting vinyl rhodium Int5 is thermodynamically less stable than the original aryl rhodium Int0 (+ 3.3 kcal mol À1 vs.0kcal mol À1 ), which may be attributed to as tronger stabilizing effect of phenyl group as well as the additional stabilizing effect from the coordination of the vinyl group in Int0.A lthough the reverse migration (Int5 ! [14] In conclusion, we have reported an asymmetric rhodiumcatalyzed alkenylation of enones and imines with arylboronic acids.Ahighly efficient aryl to vinyl 1,4-rhodium migration is the key to success,p roviding an ew mode to generate stereodefined vinylrhodium species.B oth diene and bisphosphine ligands proved to be competent to promote this rhodium migration sequence,a nd excellent enantioselectivities were also obtained with the corresponding chiral ligands. These results indicate that, unlike the previous thermodynamically favored vinyl to aryl 1,4-rhodium migration, [4] the current process is kinetically controlled, which is in accordance with the basic hypothesis assumed above.T his mechanism also explains similar aryl to vinyl 1,4-palladium migration-cross-coupling sequences.…”
Section: Angewandte Chemiementioning
confidence: 80%
“…These results indicate that, unlike the previous thermodynamically favored vinyl to aryl 1,4-rhodium migration, [4] the current process is kinetically controlled, which is in accordance with the basic hypothesis assumed above.T his mechanism also explains similar aryl to vinyl 1,4-palladium migration-cross-coupling sequences. [14] In conclusion, we have reported an asymmetric rhodiumcatalyzed alkenylation of enones and imines with arylboronic acids.Ahighly efficient aryl to vinyl 1,4-rhodium migration is…”
Section: Angewandte Chemiementioning
confidence: 80%
See 2 more Smart Citations